Comparison Of Euler Method And Runge Kutta Method In Estimation Of The Number Of Population In Aceh Province: Perbandingan Metode Euler Dan Metode Runge Kutta Dalam Estimasi Jumlah Penduduk Di Provinsi Aceh - Tarisma, Tantri; Saumi, Fazrina; Wardani, Suci; Zahara, Zahara; Kristina, Desi (Universitas Wiralodra, 2022)
Residents are people who are in an area and are controlled by applicable rules and interact with each other Residents are people who are in an area and are bound by applicable rules and interact with each other continuously or continuously. If population growth increases, this will cause many problems, including: poverty levels, unemployment, school dropout rates and increasing crime rates in each region. In anticipating the problem of increasing the population of Aceh Province, information about the population is needed. Therefore, this study will discuss several applications of mathematical methods in estimating the population of Aceh Province in the coming year using the Euler method and the Runge Kutta method of order 4. The results of the estimation of the population of Aceh Province using the Runge Kutta method are 5.030.503 inhabitants in 2021, 5.076.307 in 2022 and 5.122.486 in 2023 The estimation results using the Euler method are 5.026.162 in 2021, 5.071.745 in 2022 and 5.117.700 in 2022. The conclusion in this study is that estimation using the Runge Kutta method is a method that is better applied than the method Euler on the problem of estimating the population of Aceh Province. This is because the error value of the Runge Kutta method is smaller than the Euler method with an error value of about 0.04%. Key words : Runge Kutta, Euler, Population.